Reading extra : - Driscoll, Liz (Cambridge copy collection)
This book uses many authentic sources such as factual texts, newspaper articles, features and TV schedules, instruction manuals, everyday signs, stories, quizzes, emails and diary entries. Students are encouraged to read material on different levels and in different ways, such as reading for gist, scanning, skimming, comprehension, analysing structure, summarising and shadow reading